Strategi Pengembangan Yayasan Seri Amal Pasca Pandemi Covid-19 : Studi Kasus SMA Cahaya Medan dan SMA ST. Petrus Sidikalang - Gandaputra Simbolon, Andreas Nicholas; Fahmi, Idqan; Syafitri, Utami Dyah (Jayapangus Press, 2024)
The COVID-19 pandemic has necessitated profound changes in the field of education, triggering a shift from conventional to online learning. This research delves into the impact of the implementation of online learning systems on students' academic performance in two high schools, namely SMA Putri Cahaya Medan and SMA Santo Petrus Sidikalang, under the auspices of the Yayasan Seri Amal. Through biplot analysis and the Analytical Hierarchy Process (AHP) approach, this study identifies patterns of changes in student grades and develops strategic school development strategies. The findings indicate that although there have been no significant changes in student grades, development strategies focused on staff training, improvement of facilities and technology, and external collaborations—especially with alumni and relevant institutions—are key to maintaining competitiveness and enhancing the quality of education. The conclusions and recommendations of this research provide guidance for school management and stakeholders to design adaptive strategic measures amid the evolving dynamics of education.